Il jihadismo digitale. Libertà religiosa, sicurezza, democrazia (Stato, Chiese e pluralismo confessionale, 2023)
Digital jihadism. Freedom of religion, security, democracyABSTRACT: The Digital Revolution and the emergence of the Algorithmic Society made difficult the relationship between security and liberty. On the one hand, the digitalizing of terrorism and extremism has put in danger the public safety, due to misuse of social media and platform to radicalize (lone wolves), recruit, train or planning terrorist attacks. On the other hand, the public-private model of governance of speech has endangered the freedom of religion and speech, by permitting private actors to censure users, through AI and without the shield of the rule of law, under the cloak of freedom of contracts. This paper analyzes the state of the art, trying to draw a perimeter for the study of underlying issues and relationship between religion, democracy and security in the digital era.